The Anti‐HIV Microbicide Candidate RC‐101 Inhibits Pathogenic Vaginal Bacteria Without Harming Endogenous Flora or Mucosa. (20th November 2012) - Eade, Colleen R.; Cole, Amy L.; Diaz, Camila; Rohan, Lisa C.; Parniak, Michael A.; Marx, Preston; Tarwater, Patrick M.; Gupta, Phalguni; Cole, Alexander M.
<x xml:space="preserve">Abstract</x> Problem Vaginal microbicides represent a promising approach for preventing heterosexual HIV transmission. However, preclinical evaluation should be conducted to ensure that microbicides will be safe for human cells and healthy microflora of the female reproductive tract. One microbicide candidate, RC‐101, has been effective and well tolerated in preliminary cell culture and macaque models. However, the effect of RC‐101 on primary vaginal tissues and resident vaginal microflora requires further evaluation. Method of study We treated primary vaginal tissues and vaginal bacteria, both pathogenic and commensal, with RC‐101 to investigate effects of this microbicide. Results RC‐101 was well tolerated by host tissues, and also by commensal vaginal bacteria. Simultaneously, pathogenic vaginal bacteria, which are known to increase susceptibility to HIV acquisition, were inhibited by RC‐101. Conclusions By establishing vaginal microflora, the specific antibacterial activity of RC‐101 may provide a dual mechanism of HIV protection. These findings support advancement of RC‐101 to clinical trials.